Spatial nonuniform distribution of ²³⁵U isotope at supercritical fluid extraction with carbon dioxide in a gradient temperature field - Borts, B.V.; Skoromnaya, S.F.; Kazarinov, Yu.G.; Neklyudov, I.M.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2021)
The spatial redistribution of the ²³⁵U isotope of natural uranium in a gradient temperature field along the height of the reactor in supercritical carbon dioxide has been experimentally investigated. The scheme of the reactor is given and the principle of operation of the reactor is described. The method of preparation of initial samples from granite samples containing natural uranium and the procedure of extraction are described. The conclusion about the spatial redistribution of ²³⁵U isotopes in supercritical carbon dioxide is based on the analysis of gamma spectra of extracts. It is shown that the concentration of the ²³⁵U isotope in a supercritical fluid is maximal near the lower heated flange of the reactor, and decreases with approaching the upper, cooled flange. It was concluded that the separation factor of the ²³⁵U isotope in supercritical carbon dioxide can be about 1.2 ± 0.12.